Exploration of the Healthy Donor Effect Among 0.6 Million Blood Donors in China: Longitudinal Study - Shu Su; Yang Sun; Xiaoyun Gu; Wenjie Wu; Xiaodong Su; Ting Ma; Aowei Song; Xinxin Xie; Liqin Wang; Qianke Cheng; Lingxia Guo; Lei Zhang; et al. (JMIR Publications, 2024)
BackgroundThe World Health Organization emphasizes the importance of completely voluntary blood donation to maintain safe and sustainable blood supplies. However, the benefits of blood donation for donors, such as reducing the risk of disease, remain a topic of debate due to the existence of the healthy donor effect (HDE). This effect arises because of inherent health differences between blood donors and the general population, and it is also considered a methodological issue. ObjectiveThis study aims to generate a more detailed health profile of blood donors from a donor cohort study to mitigate and quantify the HDE and properly interpret the association between blood donation and disease outcomes among blood donors. MethodsA retrospective cohort study was conducted between January 2012 and December 2018 among donors before their first donation. One-to-one propensity score matching was conducted through a random selection of individuals without any history of blood donation, as reported from their electronic health records. We conducted a Poisson regression between blood donors and non-blood donors before the first donation to estimate the adjusted incidence rate ratio (AIRR) of selected blood donation-related diseases, as defined by 13 categories of International Classification of Diseases, Tenth Revision (ICD-10) codes. ResultsOf the 0.6 million blood donors, 15,115 had an inpatient record before their first donation, whereas 17,356 non-blood donors had an inpatient record. For the comparison between blood donors and the matched non-blood donors, the HDE (the disease incidence rate ratio between non-blood donors and blood donors) was an AIRR of 1.152 (95% CI 1.127-1.178; P<.001). Among disease categories not recommended for blood donation in China, the strongest HDE was observed in the ICD-10 D50-D89 codes, which pertain to diseases of the blood and blood-forming organs as well as certain disorders involving the immune mechanism (AIRR 3.225, 95% CI 2.402-4.330; P<.001). After age stratification, we found that people who had their first blood donation between 46-55 years old had the strongest HDE (AIRR 1.816, 95% CI 1.707-1.932; P<.001). Both male and female donors had significant HDE (AIRR 1.082, 95% CI 1.05-1.116; P=.003; and AIRR 1.236, 95% CI 1.196-1.277; P<.001, respectively) compared with matched non-blood donors. Conclusions: Our research findings suggest that the HDE is present among blood donors, particularly among female donors and those who first donated blood between the ages of 46 and 55 years. Trial RegistrationChinese Clinical Trial Registry ChiCTR2200055983; https://www.chictr.org.cn/showproj.html?proj=51760